Digital Media Use and the School Environment as Predictors of Students’ Learning Interest in Islamic Education - Andini Afiatus Sholehah; Benny Prasetiya; Abebe Tewachew (Journal of Islamic Education Research, 2025)
This study investigates the extent to which digital media use and the school environment predict students’ learning interest in Islamic Education. Amid the rapid expansion of technology-supported learning, understanding how digital media and school contexts shape student engagement has become increasingly important, particularly in faith-based education. Employing a quantitative research design, data were collected using a validated and reliable questionnaire administered to all 103 students of Integrated Islamic junior high school (SMP IT Permata Probolinggo, Indonesia) through saturated sampling. Multiple linear regression analysis was applied to examine both partial and simultaneous effects. The findings indicate that digital learning media (p = 0.003; t = 3.018) and the school environment (p = 0.005; t = 2.873) each have a significant positive effect on students’ learning interest. Simultaneously, both variables significantly predict learning interest (p = 0.000), with an R² value of 0.660, indicating that 66% of the variance in learning interest is explained by the two predictors. These results provide empirical evidence that the integration of interactive digital media and a supportive school environment plays a crucial role in enhancing students’ engagement in Islamic Education. This study contributes to the literature on digital learning in faith-based schools by offering quantitative evidence from Indonesia’s Integrated Islamic School context and highlights the importance of optimizing technology use alongside conducive learning environment.